Obligate sugar oxidation in Mesotoga spp., phylum Thermotogae, in the presence of either elemental sulfur or hydrogenotrophic sulfate‐reducers as electron acceptor. (7th December 2017) - Fadhlaoui, Khaled; Ben Hania, Wagdi; Armougom, Fabrice; Bartoli, Manon; Fardeau, Marie‐Laure; Erauso, Gaël; Brasseur, Gaël; Aubert, Corinne; Hamdi, Moktar; Brochier‐Armanet, Céline; Dolla, Alain; Ollivier, Bernard
Summary: Mesotoga prima strain PhosAc3 is a mesophilic representative of the phylum Thermotogae comprising only fermentative bacteria so far. We show that while unable to ferment glucose, this bacterium is able to couple its oxidation to reduction of elemental sulfur. We demonstrate furthermore that M. prima strain PhosAc3 as well as M. prima strain MesG1 and Mesotoga infera are able to grow in syntrophic association with sulfate‐reducing bacteria (SRB) acting as hydrogen scavengers through interspecies hydrogen transfer. Hydrogen production was higher in M. prima strain PhosAc3 cells co‐cultured with SRB than in cells cultured alone in the presence of elemental sulfur. We propose that the efficient sugar‐oxidizing metabolism by M. prima strain PhosAc3 in syntrophic association with a hydrogenotrophic sulfate‐reducing bacterium can be extrapolated to all members of the Mesotoga genus. Genome comparison of Thermotogae members suggests that the metabolic difference between Mesotoga and Thermotoga species (sugar oxidation versus fermentation) is mainly due to the absence of the bifurcating [FeFe]‐hydrogenase in the former. Such an obligate oxidative process for using sugars, unusual within prokaryotes, is the first reported within the Thermotogae . It is hypothesized to be of primary ecological importance for growth of Mesotoga spp. in the environments that they inhabit.